Activity Book As A Home Study Media In The Establishment Of Clean Healthy Living Behavior During The Covid 19 Pandemic In Preschool Age Children - Wahyu Jati Dyah Utami; Yodong Yodong; Prasko Prasko; Endah Aryati Ekoningtyas (Jurnal Kesehatan Gigi, 2021)
Background : The Clean and Healthy Behavior Movement is a benchmark in health development in order to improve people's behavior. The achievement of PHBS indicators in Central Java in 2015 was 76.73%. This makes Clean and Healthy Living Behavior (PHBS) a special concern for the government, especially during the Covid 19 pandemic. Instilling PHBS behavior in children is very important, because children's low knowledge of PHBS will affect their low body health status. Parents have a very important role in assisting children to study at home during the Covid-19 pandemic, especially in applying knowledge about clean and healthy living behavior.Research Objectives: This research is to produce learning media at home for pre-school children through activity books and analysis of their effectiveness on the formation of Healthy Clean Living Behaviors.Research Methods: Research and Development (RD), there are ten stages, namely: potential problems, data collection, product design, expert validation, revisions, product trials, usage trials (quasi-experimental with pre-test and post test design), a sample of 30 children. The treatment was carried out for 14 days, measurements were carried out pre-experimentally, after 7 days, and after 14 days. The data were tested using freadmen followed by a post hoc wilcoxon test.Results: The average knowledge about clean and healthy living behavior (hand washing, nail hygiene, dressing hygiene, dental hygiene, hair hygiene, environmental hygiene) before giving the activity book was 32.5 then after the twelfth week. -1 to 74.5 knowledge is increasing in the 2nd week of 92.99. Based on the results of statistical tests, this Activity Book has an effect on the formation of healthy clean living behavior indicated by the p value 0.001Conclusion : Activity Book is effective as an effort to establish Healthy Clean Living Behavior in pre-school children.